"A GENTE TAMBÉM TINHA CORAGEM DE ENFRENTAR" : ANÁLISE DAS ATUAÇÕES POLÍTICAS DAS TRABALHADORAS RURAIS DA REGIÃO CENTRAL DO PARANÁ (1980/1990) - Almeida, Marisangela Lins de (2015)
This text discusses the resistances of country people and the political actions of female rural workers in the context of rural unions at the municipality of Pitanga, in the central region of the State of Paraná, between the years of 1980 and 1997. The study is based on written documents and on the accounts of the life experiences of Zenóbia Cedorak, agriculturalist, unionist and teacher. Based on these sources, the study examines the places socially constructed for the female rural workers; written or spoken, both sources point to spheres that assigned women to the homes, distant from the political doing, a space historically constructed as a man`s place and that, because of this, suggests the invisibility of women as political subjects. The rural union, seen as a space of historically masculine action, despite having a policy and a base work for the inclusion of women, ended up by reproducing gender inequalities. On the other side, upon entering such spaces, the women (agriculturalists, landless women, tenants, sharecroppers, piece workers) gave meaning to their actions, putting into action many of their ideas about the world. We call attention to the details, unveiled mainly in Zenóbia`s speeches, whose memory reminiscences indicate a reedition of her functions and traditional roles in this space. The relation of women with the biblical circles is also discussed based on the oral narratives of the woman interviewed.